Barriers to Colorectal Cancer Screening: Physician and General Population Perspectives, New Mexico, 2006 - Richard M. Hoffman, MD, MPH; Robert L. Rhyne, MD, MPH; Deborah L. Helitzer, ScD; S. Noell Stone, MPH; Andrew L. Sussman, PhD, MCRP; Elizabeth E. Bruggeman, PhD, MA; Robyn Viera; Teddy D. Warner, PhD (Centers for Disease Control and Prevention, 2011)
IntroductionColorectal cancer (CRC) screening rates are low in New Mexico. We used statewide surveys of primary care physicians and the general population to characterize CRC screening practices and compare perceptions about screening barriers.MethodsIn 2006, we surveyed 714 primary care physicians in New Mexico about their CRC screening practices, beliefs, and perceptions of patient, provider, and system barriers. A 2004 state-specific CRC screening module for the Behavioral Risk Factor Surveillance System (BRFSS) survey asked 3,355 participants aged 50 years or older why they had not ever or had not recently completed a fecal occult blood test (FOBT) or lower endoscopy.ResultsThe 216 physicians (30% response rate) reported offering screening to a median 80% of their average-risk patients in the past year and estimated that a median 50% were current with screening. They attributed low screening proportions mainly to patient factors (embarrassment, fear of pain, lack of insurance). However, just 51% of physician respondents used health maintenance flow sheets, and only 13% used electronic medical records to identify patients due for CRC screening. The BRFSS respondents most often reported that lack of physician discussion was responsible for not being current with screening (45% FOBT, 34% endoscopy); being asymptomatic was also often cited as an explanation for lack of screening (22% FOBT, 36% endoscopy).ConclusionPhysicians and adults in the general population had markedly different perspectives on barriers to CRC screening. Increasing screening may require system supports to help physicians readily identify patients due for CRC testing and interventions to educate patients about the rationale for screening.